2011
DOI: 10.1172/jci42545
|View full text |Cite
|
Sign up to set email alerts
|

Pro-resolving actions and stereoselective biosynthesis of 18S E-series resolvins in human leukocytes and murine inflammation

Abstract: E-series resolvins are antiinflammatory and pro-resolving lipid mediators derived from the ω-3 polyunsaturated fatty acid eicosapentaenoic acid (EPA) that actively clear inflammation to promote tissue homeostasis. Aspirin, in addition to exerting antithrombotic actions, also triggers the biosynthesis of these specialized pro-resolving mediators. Here, we used metabolomic profiling to investigate the biosynthesis of E-series resolvins with specific chiral chemistry in serum from human subjects and present evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
311
3
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 258 publications
(323 citation statements)
references
References 57 publications
8
311
3
1
Order By: Relevance
“…These results agree with Oh et al ( 19 ) who showed that total concentration of 18-HEPE was not altered after a single dose of fi sh oil and aspirin.…”
Section: Discussionsupporting
confidence: 93%
“…These results agree with Oh et al ( 19 ) who showed that total concentration of 18-HEPE was not altered after a single dose of fi sh oil and aspirin.…”
Section: Discussionsupporting
confidence: 93%
“…Thus measurement of 18R/S-HEPE may represent total EPA-derived resolvin capacity. The enantionmers 18S-HEPE and 18R-HEPE can be resolved with baseline resolution by using chiral chromatography (19 ). Our analyses showed that 17S-HDHA and 17R-HDHA eluted as a single peak on LCMSMS and had the same fragmentation pattern (data not shown).…”
Section: Discussionmentioning
confidence: 75%
“…17,18 ), and maresins (MaR). These have been termed specialised pro-resolving mediators (SPM) since they are involved in the clearance and regulation of inflammatory substances 19,20 . Numbers in the PG and TX shorthand notation represent the number of double bonds in the molecule; the double bonds can be used for formation of cyclic-or oxy-derivatives.…”
Section: Fatty Acids As Precursors Of Lipid Mediatorsmentioning
confidence: 99%